Cross-sectional study of complement C3 as a coronary risk factor among men and women - Onat, A; Uzunlar, B; Hergenç, G; Yazici, M; Sari, I; Uyarel, H; Can, G; Sansoy, V (PORTLAND PRESS LTD, 2005)
In the present study, we examined (i) whether C3 (complement 0) was an independent marker of prevalent CHID (coronary heart disease), and (ii) which preferential associations existed between C3 and some cardiovascular risk factors when jointly analysed with CRP (C-reactive protein) and fibrinogen. In a cohort of 756 unselected adults, 39% of whom had the metabolic syndrome, C3 and other risk variables were evaluated in a cross-sectional manner. In a logistic regression model for the likelihood of CHID, a significant OR (odds ratio) of 3.5 [95% Cl (confidence intervals), 1.27 and 9.62)] for C3 was obtained after adjustment for smoking status, TC (total cholesterol) and usage of statins. A similar model, also comprising systolic blood pressure, with a cut-off point of greater than or equal to 1.6 g/l C3 exhibited a 1.9-fold risk (95 % Cl, 1.01 and 3.58) compared with individuals below the cut-off point. Both analyses displayed an adjusted OR of 1.37 for each S.D. increment in C3. The significant relationship of Q with a likelihood of CHD also proved to be independent of CRP. In multiple linear regression models, associations were tested for each acute-phase protein with measures of obesity, fasting insulin, triacylglycerols (triglycerides), TC, HDL (high-density lipoprotein)-cholesterol, physical activity, smoking status, diagnosis of metabolic syndrome and family income. When both genders were combined, C3 was independently associated with serum triacylglycerols, waist circumference, BMI (body mass index) and TC. CRP was independently associated with waist circumference, TC, family income (inversely) and physical activity, and fibrinogen with BMI, TC, smoking status and metabolic syndrome. In summary, elevated levels of complement C3 are associated with an increased likelihood of CHID independent of standard risk factors and regardless of the presence of acute coronary events, suggesting that C3 might be actively involved in coronary atherothrombosis. Unlike CRP and fibrinogen, C3 was preferentially associated with waist girth and serum triacylglycerols.
Keywords: complement C3; coronary heart disease; C-reactive protein; fibrinogen; risk factor; REACTIVE PROTEIN; CARDIOVASCULAR-DISEASE; SERUM C3; HEART-DISEASE; INFLAMMATION; ASSOCIATION; MARKERS; INSULIN; CHOLESTEROL; Research & Experimental Medicine